Pulmonary thromboembolism: a case report and misdiagnosis analysis of a 63-year-old female patient - Deng, Yingli; Lai, Jing; He, Qingmin (Frontiers in Medicine, 2024)
This paper presents a case of a 63-year-old female patient who was initially misdiagnosed with mycoplasma pneumonia due to symptoms such as chest pain, hemoptysis, and fever, but was later confirmed to have pulmonary thromboembolism (PTE) through further examination. This case highlights the similarities between PTE and pneumonia in terms of symptoms, as well as the complexity of PTE diagnosis.The article provides a detailed description of the patient's medical history, symptoms, examination process, and treatment outcomes. Furthermore, it discusses the possible reasons for the misdiagnosis, including insufficient awareness of PTE among physicians, lack of in-depth investigation into the causes of abnormally elevated D-dimer levels, the non-specific clinical manifestations of PTE, and the concerns of the patient's family regarding pulmonary artery CTA examination. Additionally, the article emphasizes the importance of clinicians in improving their ability to differentiate and diagnose PTE, rationally utilizing clinical examination methods, and ensuring timely diagnosis and treatment of PTE.Pulmonary thromboembolism (PTE) is a disease triggered by thrombi originating from the venous system or right heart, which obstruct the pulmonary arteries or their branches, leading to impairments in pulmonary circulation and respiratory function (1, 2). As one of the common cardiopulmonary vascular diseases in China (3, 4), the primary clinical manifestations of PTE include dyspnea, chest pain, and cough.However, these symptoms closely resemble the respiratory symptoms of mycoplasma pneumonia, leading to frequent misdiagnosis and subsequent missed diagnosis, which can severely impact the prognosis of patients. This paper aims to illustrate a typical case of PTE that was misdiagnosed as pneumonia.